Preparation method of aluminum nitride ceramic electrostatic chuck

By using customized powder and vibration filling technology in the preparation of aluminum nitride electrostatic chucks, combined with layered static pressure and vacuum hot press sintering, the performance defects in carbon residue and molding processes are solved, achieving high performance and high performance Integrity of electrostatic chuck preparation.

CN119260900APending Publication Date: 2025-01-07JUNYUAN ELECTRONIC TECHNOLOGY (HAINING) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411265900.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

During the semiconductor manufacturing process, during the preparation of aluminum nitride electrostatic chuck, carbon residue leads to performance defects, affecting thermal conductivity and appearance. In the existing molding process, uneven additives and high-temperature treatment can easily damage the wire mesh and reduce performance .

Method used

Using customized aluminum nitride powder with 3wt%Y2O3 added, through vibration filling and layered isostatic pressing process, combined with vacuum hot press sintering, avoid the use of binders and plasticizers, reduce carbon residue, and pass trace rare earth elements. Preparation, adjust the sintering temperature to achieve densification.

Benefits of technology

Effectively control carbon residue, improve the density and uniformity of the blank, reduce the sintering temperature, ensure the integrity and performance uniformity of the blank, avoid impurities and adhesive pollution caused by machining, and increase the heat of the electrostatic chuck Conductivity and appearance quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119260900A_ABST
    Figure CN119260900A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an aluminum nitride ceramic electrostatic chuck, which belongs to the technical field of semiconductors, and comprises the following steps: preparing aluminum nitride powder and a pressing mold; powder filling: putting the first mold plate into the bottom of the inner side of the mold body, weighing aluminum nitride powder for vibration filling, putting the flat plate on the powder subjected to vibration filling, adjusting the flat plate to be flat, putting the pore plate on the flat plate, putting the pore plate on the flat plate again, putting the second mold plate on the pore plate, and leveling the second mold plate; then filling aluminum nitride powder on a second mold plate through vibration, placing a flat plate on the aluminum nitride powder on the second mold plate, continuously placing a pore plate above the flat plate, placing a third mold plate on the pore plate, filling aluminum nitride powder on the third mold plate through vibration, placing the flat plate above the powder after powder filling, and placing the pore plate above the flat plate; the upper part of the uppermost pore plate is covered with a mold cover; and bundling, static pressing and sintering: carrying out isostatic pressing after sealing and bundling, and sintering after pressing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of semiconductor technology, and in particular to a method for preparing an aluminum nitride ceramic electrostatic chuck. Background Art

[0002] In the semiconductor manufacturing process, there are many steps in the wafer processing, such as plasma immersion, ion doping and implantation, physical and chemical vapor deposition. Each step in the processing requires the electrostatic chuck to adsorb and clamp the wafer.

[0003] Currently, electrostatic chucks are primarily manufactured using aluminum oxide and aluminum nitride (Al2O3). These materials are widely used due to their excellent insulation, dielectric properties, wear resistance, and hardness. Aluminum nitride, however, outperforms Al2O3, offering excellent thermal conductivity and insulation, a low dielectric constant, low dielectric loss, and a coefficient of expansion that closely matches the wafer, making it widely used in semiconductor manufacturing. During semiconductor manufacturing, excellent thermal conductivity ensures stable temperature uniformity across the wafer, while low resistivity results in better adsorption. Good flatness ensures more uniform adsorption across the wafer. However, the preparation and storage of Al2O3 powder are crucial. If care is not taken, the powder can absorb moisture from the air or undergo hydrolysis and oxidation due to improper storage, potentially leading to a decrease in the Al2O3 lattice during sintering.

[0004] Electrostatic chuck ceramic discs are formed and sintered using methods such as tape casting, gelcasting, dry pressing, and isostatic pressing. However, these processes often involve the addition of numerous additives and plasticizers, resulting in uneven doping during mixing and residual carbon during binder removal, which can negatively impact product performance. Trace amounts of residual carbon can reduce the oxygen content in the aluminum nitride lattice through carbothermal reactions, improving thermal conductivity. However, residual carbon exceeding 200 ppm during binder removal can easily participate in liquid-phase reactions during sintering, altering the liquid phase composition. Liquid-phase viscosity alters the resistance to pore aggregation and diffusion, leaving pores between grain boundaries, altering particle distribution, and promoting abnormal grain growth, impacting the green body's microstructure. Excessive carbon deposition can also cause discoloration, impacting product appearance and performance. While increasing the binder removal temperature can reduce carbon content to some extent, excessively high temperatures can oxidize the chuck wire mesh, degrading its performance. Therefore, residual carbon during the forming process is a major factor impacting chuck performance. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing an aluminum nitride ceramic electrostatic chuck to solve the problems raised in the background technology.

[0006] In order to solve the above technical problems, the technical solution of the present invention is:

[0007] A method for preparing an aluminum nitride ceramic electrostatic chuck, the method comprising:

[0008] Prepare materials: Customize aluminum nitride powder with a certain grade by adding 3wt% Y2O3 to prevent the influence of carbon residue on the performance of the green body;

[0009] Prepare the pressing mold: process a cylindrical mold body with an inner cavity and an opening, a cylindrical mold cover that matches the opening of the mold body, and a first mold plate, a second mold plate, a third mold plate, a hole plate, and a flat plate to be placed in the mold body. The diameters of the first mold plate, the second mold plate, the third mold plate, the hole plate, and the flat plate are equal, and the diameters of the first mold plate, the second mold plate, the third mold plate, the hole plate, and the flat plate are all equal to the diameter of the inner cavity of the mold body.

[0010] Filling powder: The first mold plate is placed into the bottom of the inner side of the mold body, and then leveled with a spirit level. The aluminum nitride powder is weighed by weight and the frequency is adjusted to 24-28 Hz for vibration filling. The flat plate is placed on the vibration-filled powder, and the flat plate is adjusted to make it flat. Then, the orifice plate is placed on the flat plate to facilitate pressure conduction and adjust the pressure balance. Then, according to the height of each layer of the electrostatic chuck ceramic piece, the same method is used to vibrate and fill powder. Specifically, the second mold plate is placed on the above-mentioned orifice plate, the second mold plate is leveled, and then ALN ​​powder is filled on the second mold plate by vibration. A flat plate is placed on the aluminum nitride powder on the second mold plate, and the orifice plate is placed on the flat plate. The third mold plate is placed on the orifice plate and ALN powder is filled on the third mold plate by vibration. After the powder filling is completed, a flat plate is placed on the powder again, and a orifice plate is placed on the flat plate. The mold cover is covered on the top orifice plate.

[0011] Bundling: After filling the powder according to the above steps, fasten the mold cover to the mold body and seal it;

[0012] Hydrostatic pressing: The sealed pressing mold is placed in a cold isostatic pressing cylinder with a cylinder diameter of φ600, and the pressure is increased in a stepwise manner to 270MPa, and the isostatic pressing is performed while holding the pressure for 300s;

[0013] Sintering: First, place the wire mesh in the groove of the pressed green body, adjust the spacing and accurately position it to ensure interference fit between the layers; then place the prepared green body in a graphite mold coated with BN powder and cover it with carbon paper. Then, hot press and sinter at 1850℃ for 4 hours in a vacuum N2 atmosphere with a pressure of 40MPa to form the ceramic disc of the electrostatic chuck;

[0014] Performance test: After sintering, the green body is machined and then the performance is tested.

[0015] Preferably, the mold body and the mold cover are made of rubber, the first mold plate, the second mold plate and the third mold plate are made of stainless steel, the orifice plate is made of polytetrafluoroethylene, and the flat plate is made of stainless steel.

[0016] Preferably, in the powder filling step, the vibration frequency during vibration filling is 26 Hz.

[0017] Preferably, the performance test includes testing the following values: density, thermal conductivity, flatness, resistance and dielectric constant.

[0018] Preferably, the density is 3.26 g / cm 3 , the thermal conductivity is 175 W / m·K, the flatness is ±1 mm, the resistance is greater than 10 12 Ω / cm, and the dielectric constant is 9.2.

[0019] The above technical solution has the following beneficial effects:

[0020] 1. No adhesive, the addition of plasticizer fundamentally controls the performance defects caused by carbon residue;

[0021] 2. Adding trace amounts of rare earth elements can effectively reduce the sintering temperature and achieve green body densification;

[0022] 3. The molding design with the cleanest dimensions avoids the mixing of impurities caused by machining process and ensures the integrity of the blank;

[0023] 4. Frequency and amplitude modulation vibration filling ensures the density and uniformity of the layered green body;

[0024] 5. Layered integrated isostatic pressing can ensure the uniformity and integrity of the layered green body pressing performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic cross-sectional structural diagram of the pressing mold of the present invention. DETAILED DESCRIPTION

[0026] The following is a further description of specific embodiments of the present invention in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is intended to facilitate understanding of the present invention and does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below may be combined with each other as long as they do not conflict with each other.

[0027] Electrostatic chucks come in Coulomb and J·R types. They secure wafers through adsorption. Because they offer uniform adsorption without warping, and their stable and long-lasting adsorption is widely used in semiconductor manufacturing, they are composed of an adsorption layer, an electrode layer, and a base layer. The manufacturing process ensures optimal formation by adding a certain percentage of adhesive. Due to the uneven mixing of materials and the debinding atmosphere and unreasonable temperature during the molding process, there will often be a certain amount of carbon residue in the blank, which affects its product performance; at the same time, different molding methods will have different effects on the overall uniformity of the product; and the product has particularly high requirements for performance such as flatness, parallelism, and positioning, such as the flatness of the adsorption layer and the temperature uniformity of the metal wire. A slight deviation will affect the overall performance and the product will be scrapped. This requires that there must be no defects in the preparation process to meet the above performance requirements. The net size isostatic pressing process can achieve uniform pressure on the layered blank to ensure its structural integrity and uniformity, and the interference fit is perfect to avoid defects caused by machining, and no adhesive is added to avoid carbon pollution; the preparation method of the present application can fully meet the technical requirements for the preparation performance of the suction cup by isostatic pressing of the layered blank as a whole to achieve the net size;

[0028] A method for preparing an aluminum nitride ceramic electrostatic chuck comprises the following steps:

[0029] Prepare materials: Customize aluminum nitride powder with a certain grade by adding 3wt% Y2O3 to prevent the influence of carbon residue on the performance of the green body;

[0030] refer to Figure 1, prepare the pressing mold: process a cylindrical mold body 1 with an inner cavity and an opening, a cylindrical mold cover 14 that matches the opening of the mold body 1, and a first mold plate 2, a second mold plate 3, a third mold plate 4, a first orifice plate 8, a second orifice plate 9, a third orifice plate 10, a first flat plate 5, a second flat plate 6 and a third flat plate 7 placed in the mold body, wherein the first orifice plate 8, the second orifice plate 9, and the third orifice plate 10 are the same in shape, structure, and material, but are located in different specific positions in the mold, the first flat plate 5, the second flat plate 6 and the third flat plate 7 are the same in shape, structure, and material, but are located in different specific positions in the mold, the diameters of the first mold plate 2, the second mold plate 3, and the third mold plate 4 are equal to the diameter of the inner cavity of the mold body 1, because the preparation method of the present application is used to prepare the electrostatic The shape of the chuck ceramic disc is disc-shaped, so the mold body 1 is cylindrical, and its inner cavity is also cylindrical. The first mold plate 2, the second mold plate 3, and the third mold plate 4 cooperate with its inner cavity, so it is also a disc-shaped structure. Similarly, the diameters of the first flat plate 5, the second flat plate 6 and the third flat plate 7, the first orifice plate 8, the second orifice plate 9, and the third orifice plate 10 are equal to the inner cavity diameter of the mold body 1. Different layered green bodies are prepared by the first mold plate 2, the second mold plate 3, and the third mold plate 4. Specifically, the aluminum nitride powder in the space between the first mold plate 2 and the first flat plate 5 is pressed into a first green body 11, the aluminum nitride powder in the space between the second mold plate 3 and the second flat plate 6 is pressed into a second green body 12, and the aluminum nitride powder in the space between the third mold plate 4 and the third flat plate 7 is pressed into a third green body 13;

[0031] Filling powder: The first mold plate 2 is placed into the bottom of the inner side of the mold body 1, and then leveled with a spirit level. The aluminum nitride powder is weighed by weight and the frequency is adjusted to 24-28 Hz for vibration filling. The first flat plate 5 is placed on the vibration-filled aluminum nitride powder, and the first flat plate 5 is adjusted to make it flat. Then, the first orifice plate 8 is placed on the first flat plate 5 to facilitate pressure conduction and adjust the pressure balance. Then, according to the height of each layer of the electrostatic chuck ceramic piece, the same method is used to vibrate and fill powder. Specifically, the second mold plate 3 is placed on the above-mentioned first orifice plate 8, and the second mold plate 3 is leveled. Then, aluminum nitride powder is filled on the second mold plate 3 by vibration. The second flat plate 6 is placed on the aluminum nitride powder on the second mold plate 3, and the second orifice plate 9 is placed on the second orifice plate 9. The third mold plate 4 is placed on the third mold plate 4. Aluminum nitride powder is filled on the third mold plate 4 by vibration. After the powder filling is completed, the third flat plate 7 is placed on the powder, and the third orifice plate 10 is placed on the third flat plate 7. The mold cover 14 is covered on the top third orifice plate 10.

[0032] Bundling: After the powder filling is completed according to the above steps, the mold cover 14 is fastened to the mold body 1 and sealed and bundled;

[0033] Hydrostatic pressing: The sealed pressing mold is placed in a cold isostatic pressing cylinder with a cylinder diameter of φ600, and the pressure is increased in a stepwise manner to 270 MPa. The pressure is maintained for 300 seconds and isostatic pressing is performed to press the first green body 11, the second green body 12, and the third green body 13 into a ceramic green body, so as to facilitate the next step of sintering.

[0034] Sintering: First, place the wire mesh in the groove of the pressed green body, adjust the spacing and accurately position it to ensure interference fit between the green bodies. The interference fit can make the gaps between the first green body 11, the second green body 12, and the third green body 13 very small to ensure the integrity and consistency of the green bodies. Place the prepared green body in a graphite mold coated with BN powder and lined with carbon paper. Hot press sintering is carried out at 1850°C for 4 hours in a vacuum N2 atmosphere at a pressure of 40 MPa.

[0035] Performance test: After sintering, the green body is machined and then tested for performance. The performance test is used to determine whether the prepared electrostatic chuck ceramic disc meets the requirements and verify the reliability of its preparation process;

[0036] Among them, the mold body and the mold cover are made of rubber, the first mold plate 2, the second mold plate 3, and the third mold plate 4 are all made of stainless steel, the first orifice plate 8, the second orifice plate 9, and the third orifice plate 10 are made of polytetrafluoroethylene, and the first flat plate 5, the second flat plate 6, and the third flat plate 7 are all made of stainless steel;

[0037] In the above powder filling step, the vibration frequency during vibration filling is 26 Hz;

[0038] The test performance includes testing the following values: density, thermal conductivity, flatness, resistance and dielectric constant. The electrostatic chuck ceramic disk prepared by the above method has a density of 3.26g / cm3, a thermal conductivity of 175W / m·K, a flatness of ±1mm, a resistance greater than 1012Ω / cm, and a dielectric constant of 9.2.

[0039] Compared with existing technologies, this method has the following advantages: no binder, and the addition of plasticizer fundamentally controls the performance defects caused by carbon residue; the addition of trace rare earth elements can effectively reduce the sintering temperature and achieve green body densification; the clean-cut molding design eliminates impurities caused by machining processes, ensuring the integrity of the green body; frequency and amplitude modulation vibration filling ensures the density and uniformity of the layered green body;

[0040] Layered integrated isostatic pressing can ensure the uniformity and integrity of the layered green body pressing performance.

[0041] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. It is apparent to those skilled in the art that various changes, modifications, substitutions, and variations to these embodiments may be made without departing from the principles and spirit of the present invention, and these changes and modifications still fall within the scope of protection of the present invention.

Claims

1. A method for preparing an aluminum nitride ceramic electrostatic chuck, characterized in that: The preparation method comprises: Prepare materials: Customize aluminum nitride powder with a certain grade by adding 3wt% Y2O3 to prevent the influence of carbon residue on the performance of the green body; Prepare the pressing mold: process a cylindrical mold body with an inner cavity and an opening, a cylindrical mold cover matched with the opening of the mold body, and a first mold plate, a second mold plate, a third mold plate, a hole plate and a flat plate placed in the mold body for use, wherein the diameters of the first mold plate, the second mold plate, the third mold plate, the hole plate and the flat plate are equal, and the diameters of the first mold plate, the second mold plate, the third mold plate, the hole plate and the flat plate are all equal to the diameter of the inner cavity of the mold body; Filling powder: the first mold plate is placed into the bottom of the inner side of the mold body, and then leveled with a spirit level, aluminum nitride powder is weighed by weight and the frequency is adjusted to 24-28 Hz for vibration filling, a flat plate is placed on the powder filled with vibration, the flat plate is adjusted to make it flat, and then a hole plate is placed on the flat plate to facilitate pressure conduction and adjust the pressure balance, and then the powder is vibrated and filled in the same way according to the height of each layer of the electrostatic chuck ceramic sheet, specifically: the second mold plate is placed on the above-mentioned hole plate, the second mold plate is leveled, and then aluminum nitride powder is filled on the second mold plate by vibration, and a flat plate is placed on the aluminum nitride powder on the second mold plate, and a hole plate is placed on the flat plate, and aluminum nitride powder is filled on the third mold plate by vibration. After the powder filling is completed, a flat plate is placed on the powder, and a hole plate is placed on the flat plate, and a mold cover is placed on the top hole plate; Bundling: After filling the powder according to the above steps, fasten the mold cover to the mold body and seal it; Hydrostatic pressing: The sealed pressing mold is placed in a cold isostatic pressing cylinder with a cylinder diameter of φ600, and isostatic pressing is performed by stepwise pressurization to 270MPa and pressure is maintained for 300s; Sintering: First, place the wire mesh in the groove of the pressed green body, adjust the spacing and accurately position it to ensure interference fit between the layers; place the prepared green body in a graphite mold coated with BN powder, cover it with carbon paper, and hot press sinter it in a vacuum N2 atmosphere at 1850℃, keep warm for 4 hours, and pressure 40MPa; Performance test: After sintering, the green body is machined and then the performance is tested.

2. The method for preparing an aluminum nitride ceramic electrostatic chuck according to claim 1, characterized in that: The mold body and the mold cover are both made of rubber, the first mold plate, the second mold plate and the third mold plate are all made of stainless steel, the orifice plate is made of polytetrafluoroethylene, and the flat plate is made of stainless steel.

3. The method for preparing an aluminum nitride ceramic electrostatic chuck according to claim 2, characterized in that: In the powder filling step, the vibration frequency during vibration filling is 26 Hz.

4. The method for preparing an aluminum nitride ceramic electrostatic chuck according to claim 1, characterized in that: The test performance includes testing the following values: density, thermal conductivity, flatness, resistance and dielectric constant.

5. The method for preparing an aluminum nitride ceramic electrostatic chuck according to claim 4, characterized in that: The density is 3.26 g / cm3, the thermal conductivity is 175 W / m·K, the flatness is ±1 mm, the resistance is greater than 1012 Ω / cm, and the dielectric constant is 9.2.

Citation Information

Cited By

  • Steel lining polytetrafluoroethylene workpiece machining method based on isostatic pressing forming and steel pore plate structure

    CN121715557A